2020
DOI: 10.3389/fmed.2020.00171
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Secondary Transmission Pattern and Epidemic Prediction of COVID-19 in the Four Metropolitan Areas of China

Abstract: Understanding the transmission dynamics of COVID-19 is crucial for evaluating its spread pattern, especially in metropolitan areas of China, as its spread could lead to secondary outbreaks. In addition, the experiences gained and lessons learned from China have the potential to provide evidence to support other metropolitan areas and large cities outside China with their emerging cases. We used data reported from January 24, 2020, to February 23, 2020, to fit a model of infection, estimate the likely number of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 17 publications
0
24
1
2
Order By: Relevance
“…On the topic tracking analysis of epidemiology and public health interventions, we found that most of the early studies and reports were mainly focus on China's epidemic prevention and control. [ 38 , 39 ] By implementing a series of preventive control and medical treatment measures, the pandemic in China had been effectively contained, but the number of confirmed cases outside China continued to increase, as did the corresponding research on epidemiology and public health interventions, which was consistent with the continuously high popularity trending curve of this topic (blue curve), as displayed in Figure 6 .…”
Section: Resultsmentioning
confidence: 64%
“…On the topic tracking analysis of epidemiology and public health interventions, we found that most of the early studies and reports were mainly focus on China's epidemic prevention and control. [ 38 , 39 ] By implementing a series of preventive control and medical treatment measures, the pandemic in China had been effectively contained, but the number of confirmed cases outside China continued to increase, as did the corresponding research on epidemiology and public health interventions, which was consistent with the continuously high popularity trending curve of this topic (blue curve), as displayed in Figure 6 .…”
Section: Resultsmentioning
confidence: 64%
“…These can be taken as useful measures to evaluate the effectiveness of control policies and actions against the spreading of infectious diseases. Recently, several dynamical models have been presented to describe the dynamics of the evolution of COVID-19 and trying to predict the duration of epidemics and the number of infected individuals in different countries [4,5,6,7,8,9,10,11]. Note that COVID-19 as a disease caused by a new virus needs a model taking into consideration its known specic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Using the Glob al Epidemic and Mobility Model, a study reported that the travel restrictions in Wuhan on January 23, 2020, had marked effects on reducing the spread of the new coronavirus infection globally, with an 80% importation reduction until mid-February (Chinazzi et al, 2020). Based on a dynamic transmission model, public health interventions were found to be effective in reducing the risk of 2019-nCoV spread (Su et al, 2020). Based on the regression method, a study found that, without the lockdown in Wuhan, the infected cases in other Hubei cities, excluding Wuhan, would have increased by 52.6% on February 29 (Fang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%